2000
DOI: 10.5014/ajot.54.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the Perspectives of Persons With Schizophrenia Regarding Quality of Life

Abstract: Although the findings confirm the importance of factors included in existing quality-of-life assessments, they also highlight the need to look at new dimensions of commonly included factors and to include other factors. The findings support beliefs regarding occupation that are central to occupational therapy and the use of occupation as means and ends of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
0
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 40 publications
3
107
0
3
Order By: Relevance
“…The present study identified the importance of being able to contribute to otherspartners, assistants, families, friends and communities -in reciprocal relationships that foster perceptions of value and competence, connecting and belonging, a finding supported by other researchers. 1,32,33,73,[77][78][79][80][81][82][83][84][85] The important role that special people had played in encouraging autonomy, affirming value and worth and facilitating engagement in meaningful occupations suggests that the rehabilitation process would benefit from the conscious and deliberate inclusion of friends and families. If relationships with special people provide opportunities for reciprocity and for engaging in meaningful occupations following discharge it makes little sense to exclude these people from the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified the importance of being able to contribute to otherspartners, assistants, families, friends and communities -in reciprocal relationships that foster perceptions of value and competence, connecting and belonging, a finding supported by other researchers. 1,32,33,73,[77][78][79][80][81][82][83][84][85] The important role that special people had played in encouraging autonomy, affirming value and worth and facilitating engagement in meaningful occupations suggests that the rehabilitation process would benefit from the conscious and deliberate inclusion of friends and families. If relationships with special people provide opportunities for reciprocity and for engaging in meaningful occupations following discharge it makes little sense to exclude these people from the rehabilitation process.…”
Section: Discussionmentioning
confidence: 99%
“…This means a loss of financial security, with large debts potentially building up (Krupa et al, 2010). This can then impact adversely on participant's living arrangements (Browne & Courtney, 2005b;Laliberte-Rudman et al, 2000), creating eviction fears and a loss of personal safety; "I got raped one night, no-one came, even though I screamed" (Warren & Bell, 2009, p. 198).…”
Section: Sub-theme Iv: the Loss Of Security In Body And Worldmentioning
confidence: 99%
“…Self-esteem can be lost due to the content of voices and delusions (Rhodes et al, 2005), loss of employment (Bassett et al, 2001;Mackrell & Lavender, 2004) and labeling/stigma (Laliberte-Rudman et al, 2000;Lloyd et al, 2005;MacDonald et al , 2005;Rice, 2008). This is often internalized resulting in participants judging "themselves as useless, incapable or insane" (Wagner & King, 2004, p. 143).…”
Section: Sub-theme Ii: the Loss Of Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…Hasselkus (2002) has stressed that engagement in occupation for the sake of the experience, for how someone feels when doing, is equally if not more important than its outcome or purpose. A significant theme in the literature is the call for more in-depth and process-focused research, in which the actual experience and making of meaning through occupational engagement is explored in the context of recovery from mental illness (Aubin, Hachey, & Mercier., 1999;Hasselkus, 2002;Laliberte-Rudman et al, 2000;Leufstadius et al, 2008). For example, Bejerholm and Eklund (2006) emphasized the need "to study the possible relationships between occupational engagement and the illness process, symptomatology, and the recovery of self" (p. 117).…”
mentioning
confidence: 99%